Fikih Kebinekaan,Pandangan Islam Indonesia tentang Umat, Kewargaan, dan Kepemimpinan Non Muslim - Hilman Latief (mizan, 2015)
Fikih Kebinekaan,Pandangan Islam Indonesia tentang Umat, Kewargaan, dan Kepemimpinan Non Muslim